The Case of Oral Corrective Feedback in EFL Classroom at Universitas Yapis Papua - Tenri Ugi Irianto (Ethical Lingua: Journal of Language Teaching and Literature, 2022)
Feedback plays a significant role for all levels of students to improve their English Foreign language learning. Effective feedback allows lecturers to tap into a powerful means of helping them get better at learning. The purposes of the study are to investigate which oral feedback is used most frequently and which approach is preferred use by most lecturers. So, the data has been collected through the research instruments such as survey questionnaires and classroom observation, Then, collected data has been analysed by both qualitative methods. After analyzing the responses of lecturers and classroom observation, it is found by the researcher that Universitas Yapis Papua lecturers like to indicate students' errors in clear ways or sometimes directly to the students. That's why "recasts" feedback is used most frequently by most of the lecturers in Universitas Yapis Papua and most of the lecturers preferred to use "recasts" as effective feedback in their classroom in the Universitas Yapis Papua context.